DEWAN DIREKSI, DEWAN KOMISARIS, KOMITE AUDIT, DEBT TO ASSET RATIO, DAN UKURAN PERUSAHAAN PADA RETURN ON ASSETS (ROA) - Laula Dwi Marthika; Siti Mudawanah (Universitas La Tansa Mashiro, 2026)
This study examines the effect of the board of directors, board of commissioners, audit committee, debt to asset ratio, and firm size on Return on Assets (ROA). The study applies a quantitative approach and uses multiple linear regression to test the relationship between the independent variables and ROA. The findings show that the board of directors, board of commissioners, and debt to asset ratio have a negative and significant effect on ROA, while the audit committee and firm size have a positive and significant effect on ROA. Simultaneously, all independent variables significantly affect ROA, and the model explains 90.6% of the variation in ROA.